Novel surface optimization for trajectory reconstruction in industrial robot tasks. (14th December 2021) - Funes-Lora, Miguel Angel; Vega-Alvarado, Eduardo; Rivera-Blas, Raúl; Calva-Yáñez, María Barbara; Sepúlveda-Cervantes, Gabriel
This study presents a novel algorithm implementation that optimizes manually recorded toolpaths with the use of a 3D-workpiece model to reduce manual error induced. The novel algorithm has three steps: workpiece declaration, manual toolpath declaration, and toolpath optimization using steepest descent algorithm. Steepest descent finds the surface route wherein the manually recorded toolpaths traverse over a 3D-workpiece surface. The optimized toolpaths were simulated and tested with an industrial robot showing minimal error compared to the desired optimized toolpaths. The results obtained from the presented implementation on three different trajectories demonstrate that the proposed methodology can reduce the manual error induced using as a reference the CAD-workpiece surface.